Childhood Emotional Neglect Is Associated With Low Social Support in Chinese Patients With Major Depressive Disorder - Qin, Xuemei; Wang, Mi; Lu, Xiaowen; Sun, Jinrong; Dong, Qiangli; Zhang, Liang; Liu, Jin; Ju, Yumeng; Wan, Ping; Guo, Hua; Zhao, Futao; Zhang, Yan; et al. (Frontiers in Psychiatry, 2021)
Background: Previous studies have shown that childhood maltreatment (CM) is closely associated with social support in the general population. However, little is known about the associations of different types of CM with social support in Chinese patients with major depressive disorder (MDD), which was the goal of the current study. Methods: One hundred and sixty-six patients with moderate-to-severe MDD were enrolled. Participants were assessed by the Childhood Trauma Questionnaire-28 item Short Form, Social Support Rating Scale (SSRS), the 24-item Hamilton rating scale for depression, and the 14-item Hamilton Anxiety Rating Scale. Correlation analysis and Hierarchical multiple linear regression analysis were adopted to investigate associations of types of CM with social support. Results: 1) Physical neglect (PN) and emotional neglect (EN) were the most commonly reported types of CM in patients with MDD. 2) EN was the only type of CM significant in the regression models of the SSRS total score, the score of subjective support, and the score of utilization of support. Limitations: The data of CM was collected retrospectively and recall bias may be introduced. Assessment of CM and social support were self-reported and could be influenced by the depression status. Conclusion: In Chinese patients with MDD, PN and EN are the most prevalent types of CM. EN is the only type of CM associated with low social support in regression models, calling for special attention in the assessment and intervention of EN.